Domestic violence victims’ perception on health personnel’s attendance - Cristina, Irene (2019)
Introduction: women victim of Domestic Violence search, in healthcare services a resource which can provide support in the critical situation. Objective: To describe the victim’s perception on the attendance, in the hospital environment, at the time of the violence episode. Methods: quantitative approach, descriptive, transversal. Convenience sample of 81 women housed in shelter-houses, with ages between 19-64 years old (SD=11.64). The questionnaire collected sociodemographic data and the history of victimization. Items regarding the evaluation of the attendance were applied, adapted from the Chicago programme. Ethical aspects were considered. Results: Violence occurs between 5 and 10 years to majority (n=19; 23,5%). Regarding the health professionals’ actions in relational aspects, it is observed that the majority of women has a positive perception related to the given attention (n=51; 63%). Regarding the knowledge of the professionals, the victims’ perception values the knowledge of legislation (n=75; 92.6%). Regarding the efficacy of attendance, the item utility of referral by the professionals is highlighted (n=72; 88.9%). Conclusion: Results regarding attendance are positive. However, in the victims’ perception, the professionals don’t possess a total easiness when speaking face-to-face about violence with the victim. Regarding the safety plan, it is desirable a better co-construction between victim and professional